Kewenangan Khusus Otorita Ibu Kota Nusantara dalam Sistem Tata Usaha Negara di Indonesia - Pramono, Budi; Latif, Abdul; Setyowati, Retno Kus (VISA: Journal of Vision and Ideas, 2025)
In 2019, President Joko Widodo announced the plan to relocate Indonesia's capital to East Kalimantan. This project aims to improve regional governance and reflect the nation's identity and unity. With a budget of Rp466 trillion, the project involves various funding schemes. The Nusantara Capital Authority (OIKN) was established to manage the preparation, construction, and relocation of the new capital, as well as to administer the special regional government. This study aims to analyze the legal status of OIKN and the legal implications of its regulations in managing the capital city. Using normative and descriptive legal methods, the study evaluates OIKN's special authority within Indonesia's state administration system and its legal implications. The research reveals that OIKN, established under Law No. 21 of 2023 and Presidential Decree No. 62 of 2022, functions as a special regional government institution under Article 18B of the 1945 Constitution. Although the head of the authority is appointed directly by the president and not elected by the Regional People's Representative Council (DPRD), OIKN has broad powers, including in investment licensing, spatial planning, and development. While this system is expected to expedite development and provide legal certainty, the potential conflicts with regional governments and criticism of relocating the capital from Jakarta to IKN highlight the challenges and complexities of implementing the project, including concerns about budget and legal certainty for investors.